A Novel Directly Compressible Co-Processed Excipient for Sustained Release Formulation - Avinash Gangurde, Rahul Kashinath Patole, Ajay Kumar Sav, Purnima Dharnraj Amin (Journal of Applied Pharmaceutical Science, 2013)
A novel directly compressible (DC) co-processed excipient with improved functionality and masking the undesirable properties of individual excipients was developed without any chemical modification by using simple laboratory technique. For the development of co-processed excipient, release retarding polymers such as Polyethylene oxide (Polyox® WSR 301) and hydroxyl propyl methyl cellulose (Methocel® K4M) were used. Co-processed excipient was prepared in polymers weight ratio of 1:9 to 9:1 by roller compaction technique. Co-processed excipient prepared from polymers ratio of 7:3 and 8:2 showed good physico-chemical properties. The developed DC grade co-processed excipient was characterized for DSC, FTIR, SEM, XRD which confirms the absence of any chemical changes during co-processing. Highly water soluble Metoprolol succinate and poorly water soluble anhydrous Theophylline was used as model drugs for Invitro release study. Formulations prepared using co-processed excipient showed sustain drug release in which initial burst release was controlled by polyethylene oxide and HPMC controls the extended drug release. Developed formulations were kept for stability study for three month as per ICH guidelines and found to be stable. Study indicates that use co-processed excipient has added advantage over polymer with single property and can be used in sustain release formulation irrespective of drug type.
Keywords: Polyethylene oxide, hydroxyl propyl methyl cellulose